The Dwelling Place of Light $1 (BCompletes - Churchill, Winston, 1871-1947 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Dwelling Place of Light $1 (BComplete" by Winston Churchill is a novel written in the early 20th century. It explores themes of economic displacement, social change, and familial struggles through the experiences of Edward Bumpus, a middle-aged man who, having fallen from a once-respected position in society, now finds himself as the gatekeeper of a mill in a gritty industrial city. The narrative delves deep into the lives of Edward and his family, capturing their tensions and aspirations amid a rapidly changing America. The opening of the book introduces us to Edward Bumpus, who reflects on the loss of his family's legacy and their transition to a life in Hampton, surrounded by the oppressive environment of industry and immigrant communities. Struggling with feelings of failure and bewilderment, Edward grapples with his ancestry and identity, while his wife Hannah embodies a grim fatalism about their new life. Their daughters, Janet and Lise, approach the world differently; Janet feels confined and yearns for beauty and adventure, while Lise seemingly embraces the modern, romantic aspirations of youth. This contrast sets up a rich interplay of character dynamics and societal commentary, immersing the reader in the family's intricate emotional landscape amidst the backdrop of industrial America. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Dwelling-Place_of_Light
Release date is 2004-10-15
Produced by David Widger
Keywords: New England -- Social life and customs -- Fiction; Strikes and lockouts -- Fiction; Working class women -- Fiction; Textile industry -- Fiction